Strategy Analysis of Financing Management Quality toward Performance Improvement of Islamic Higher Education in Lampung - Tulus Suryanto; Siti Patimah (STKIP Singkawang, 2019)
The purpose of this study was to determine the formulation of strategies for improving the quality of management performance at Islamic Higher Education in Lampung, knowing the planning process and implementation of strategies carried out by Islamic Higher Education in Lampung, knowing leadership and management behavior in meeting the expectations of Islamic University Stakeholders in Lampung and knowing the suitability of the quality of the management performance of the preferences of the Management Stakeholders and Staff of Islamic Universities in Lampung. Data collection techniques in this study used a questionnaire and data analysis techniques with a qualitative approach. The results showed that the two Universities in Lampung in the formulation of strategies for improving the quality of performance have not been systematic, changes in the strategic environment have not been followed by proactive steps; the process of implementing the strategy has not been carried out maximally in the allocation of available resources; based on strategic management, the two institutions are still influenced by bureaucratic culture and low adjustments to change; Islamic tertiary institutions in Lampung have negative or maximum gaps in the role of leadership.